Characteristics of pleural effusion in IgG4-related pleuritis. (2020) - Saito, Zenya; Yoshida, Masahiro; Kojima, Ayako; Tamura, Kentaro; Kuwano, Kazuyoshi
Abstract: Here we describe the case of a 78-year-old man with respiratory failure and right pleural effusion. Computed tomography showed right pleural effusion with pleural calcification, tumor-like shadows induced by passive atelectasis, and enlarged mediastinal lymph nodes. Positron emission tomography showed right pleural thickening, rounded atelectasis, and enlarged mediastinal lymph nodes, without fluid accumulation in other organs. The pleural effusion showed lymphocyte-dominated exudates with elevated adenosine deaminase (ADA) levels. Tuberculous pleuritis was suspected, but thoracoscopic pleural biopsy revealed lymphoplasmacytic infiltration and fibrosis, with 10 immunoglobulin G4 (IgG4)-positive plasma cells/high-power field, and IgG4/IgG ratio of 40%. IgG4 concentrations in serum and right pleural effusion were 929 and 1120 mg/dL, respectively. The patient was diagnosed with IgG4-related pleuritis without other systemic manifestations, and reduction in right pleural effusion was confirmed by corticosteroid therapy. IgG4-related disease is typically a systemic disease causing lymphoplasmacytic inflammation in multiple organs. We describe a rare form of IgG4-related pleuritis showing pleural effusion with no other systemic manifestation.